PERENCANAAN STRATEGIS LAYANAN PERPUSTAKAAN BERBASIS TEKNOLOGI INFORMASI Studi Kasus di Pusat Perpustakaan dan Penyebaran Teknologi Pertanian (Strategic planning of library services based on information technology at Indonesian Center for Agricultural Libr - Listina Setyarini; Wisnu Ananta Kusuma; Sri Wahjuni (Perpustakaan IPB, 2017)
AbstractIndonesian Center for Agricultural Library and Technology Dissemination (ICALTD), as an institution library, has a function in providing information for supporting research and development in agriculture. Information technology has been used for supporting many library services at ICALTD. However, the implementation has not referred to a comprehensive and integrated strategic planning. A good strategic planning of information technology has an impact to the successful of utilizing information technology in the library. Therefore, this research aims to develop a strategic plan of IT-based library services at ICALTD based on the IT-IL V3 framework. The strategic assessment was conducted to analyze the external and internal factors through user surveys and interviews. The respondents were selected based on the organizational structure using SWOT analysis. Moreover, the survey results were analyzed using importance performance analysis (IPA) and user satisfaction index methods. In this research, several objectiveswas determined based on the importance and performance matrix diagram and the internal analysis results. In addition, this research recommended some improvements such as: 1) developing online catalog; 2) improving the library website; 3) developing library collections; 4) conducting user training for improving electronic services and 5) increasing access to internet. Keywords: Importance Performance Analysis, Iformation Technology, IT-IL V3, Library Services, Service Strategy, Strategic Planning, User Satisfaction Index